PANCASILA SEBAGAI "SCREENING BOARD" DALAM MEMBANGUN HUKUM DI TENGAH ARUS GLOBALISASI DUNIA YANG MULTIDIMENSIONAL - Kuat Puji Prayitno (Jurnal Dinamika Hukum, 2011)
Globalization implies a deep and occurs in all aspects of life. Faced with the problems of globali-zation, the development of national law must be put Pancasila as the "margin of appreciation" or even "screening board" which will have implications in the formation of legal theory and practice of law in Indonesia. The challenge is how a nation capable of protecting its national interests (national interest) in the middle of the global atmosphere and make the local values as "screening board" in the institutionalization of universal values. Five Principles for the Indonesian nation is the core philosophy, which is a local genius and local wisdom of Indonesia. Therefore Pancasila as a source of value to the legal system. Thus, Pancasila is also an ideal law (rechts idee) is understood as the legal construction of thought that leads to the desired goal. Keywords: Pancasila, grundnorm, globalization